XoxF encoding an alternative methanol dehydrogenase is widespread in coastal marine environments. (25th June 2015) - Taubert, Martin; Grob, Carolina; Howat, Alexandra M.; Burns, Oliver J.; Dixon, Joanna L.; Chen, Yin; Murrell, J. Colin
Summary: The xox F gene, encoding a pyrroloquinoline quinone‐dependent methanol dehydrogenase, is found in all known proteobacterial methylotrophs. In several newly discovered methylotrophs, XoxF is the active methanol dehydrogenase, catalysing the oxidation of methanol to formaldehyde. Apart from that, its potential role in methylotrophy and carbon cycling is unknown. So far, the diversity of xox F in the environment has received little attention. We designed PCR primer sets targeting clades of the xoxF gene, and used 454 pyrosequencing of PCR amplicons obtained from the DNA of four coastal marine environments for a unique assessment of the diversity of xoxF in these habitats. Phylogenetic analysis of the data obtained revealed a high diversity of xoxF genes from two of the investigated clades, and substantial differences in sequence composition between environments. Sequences were classified as being related to a wide range of both methylotrophs and non‐methylotrophs from A lphaproteobacteria, B etaproteobacteria and G ammaproteobacteria . The most prominent sequences detected were related to the family R hodobacteraceae, the genus M ethylotenera and the OM43 clade of M ethylophilales, and are thus related to organisms that employ XoxF for methanol oxidation. Furthermore, our analyses revealed a high degree of so far undescribed sequences, suggesting a high number of unknown bacterial species in these habitats.